Neutrophils with low production of reactive oxygen species are activated during immune priming and promote development of arthritis - Chen, Tao; Zhou, Zhen; Liu, Yi; Xu, Jiayi; Zhu, Chenxi; Sun, Rui; Hu, Huifang; Liu, Yan; Dai, Lunzhi; Holmdahl, Rikard; Herrmann, Martin; Zhang, Lulu; et al. (Redox Biology, 2024)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease mediated by immune cell dysfunction for which there is no universally effective prevention and treatment strategy. As primary effector cells, neutrophils are important in the inflammatory joint attack during the development of RA. Here, we used single-cell sequencing technology to thoroughly analyze the phenotypic characteristics of bone marrow-derived neutrophils in type II collagen (COL2)-induced arthritis (CIA) models, including mice primed and boosted with COL2. We identified a subpopulation of neutrophils with high expression of neutrophil cytoplasmic factor 1 (NCF1) in primed mice, accompanied by a characteristic reactive oxygen species (ROS) response, and a decrease in Ncf1 expression in boosted mice with the onset of arthritis. Furthermore, we found that after ROS reduction, arthritis occurred in primed mice but was attenuated in boosted mice. This bidirectional effect of ROS suggested a protective role of ROS during immune priming. Mechanistically, we combined functional assays and metabolomics identifying Ncf1-deficient neutrophils with enhanced migration, chemotactic receptor CXCR2 expression, inflammatory cytokine secretion, and Th1/Th17 differentiation. This alteration was mainly due to the metabolic reprogramming of Ncf1-deficient neutrophils from an energy supply pathway dominated by gluconeogenesis to an inflammatory immune pathway associated with the metabolism of histidine, glycine, serine, and threonine signaling, which in turn induced arthritis. In conclusion, we have systematically identified the functional and inflammatory phenotypic characteristics of neutrophils under ROS regulation, which provides a theoretical basis for understanding the pathogenesis of RA, to further improve prevention strategies and identify novel therapeutic targets.
CRIS-Team Scopus Importer:2024-11-08
Keywords: NADPH oxidase 2; Neutrophil cytoplasmic factor 1; Neutrophils; Reactive oxygen species; Rheumatoid arthritis